Effect of Corporate Governance, Leverage and Dividend Policy on the Firm Value of Nepalese Commercial Banks - Poudyal, Rasmi; Guragain, Prashant; Pokhrel, Prasiddha; Sah, Puja; Giri, Ranjana; Pradhan, Radhe Shyam (Nepalese Journal of Management, 2025)
The study examines the effect of corporate governance, leverage and dividend policy on the firm value of Nepalese commercial banks. Market price per share and return on equity are selected as the dependent variables. The selected independent variables are board size, board independence, foreign ownership, gender diversity, dividend payout ratio, dividend per share, debt to equity ratio and debt to assets ratio. The study is based on secondary data of 10 commercial banks with 100 observations for the period from 2012/13 to 2021/22. The data were collected from Banking and Financial Statistics published by Nepal Rastra Bank, publications and websites of Nepal Rastra Bank (NRB) and annual reports of the selected commercial banks. The correlation coefficients and regression models are estimated to test the significance and importance of corporate governance, leverage and dividend policy on the firm value of Nepalese commercial banks. The study showed that gender diversity has a positive impact on market price per share and return on equity. It implies that increase in female board directors leads to increase in market price per share and return on equity. However, board size has a negative impact on market price per share and return on equity. It means that increase in board size leads to decrease in market price per share and return on equity. Similarly, the study showed that board independence has a positive impact on market price per share and return on equity. It implies that increase in number of independent directors in board leads to increase in market price per share and return on equity. Likewise, debt to equity ratio has a positive impact on market price per share and return on equity. It implies that increase in debt-to-equity ratio leads to increase in market price per share and return on equity. In addition, dividend per share has a positive impact on market price per share and return on equity. It implies that increase in dividend per share leads to increase in market price per share and return on equity. However, debt to assets ratio has a negative impact on market price per share and return on equity. It shows that increase in debt to assets ratio leads to decrease in market price per share and return on equity. Further, dividend payout ratio has a negative impact on market price per share and return on equity. It shows that increase in dividend payout ratio leads to decrease in market price per share and return on equity.